Analisis Indeks Pasar Saham Global terhadap ISSI: Studi pada DJIA, Nikkei 225, dan SSEC dengan Pendekatan Error Correction Model - Ermawati, Saffitri; Nurhadi, Bayu (Journal of Economics Research and Policy Studies, 2025)
This study aims to analyze the influence of the Dow Jones Industrial Average (DJIA), Nikkei 225, and Shanghai Stock Exchange Composite (SSEC) indices on the Indonesian Sharia Stock Index (ISSI) in both the long and short term, spanning the period from January 2015 to December 2024. This study utilizes secondary data and employs a quantitative approach, utilizing the Error Correction Model (ECM) method. The results indicate that, in the long term, the DJIA and SSEC have a significant negative impact on the ISSI. In contrast, the Nikkei 225 has a significant positive impact on the ISSI. In the short term, the DJIA has a significant positive impact on the ISSI, while the Nikkei 225 and SSEC have no significant impact on the ISSI. The results of this study indicate that the Nikkei 225 index influences the Indonesian Sharia Stock Index (ISSI) in the long term and the DJIA index in the short term. These findings underscore the importance of considering global market dynamics, particularly in Japan and the United States, as a reference for making Sharia investment decisions in Indonesia to anticipate fluctuations and capitalize on market growth opportunities.